2005
DOI: 10.1002/bsl.644
|View full text |Cite
|
Sign up to set email alerts
|

The intelligence community and the war on terror: the role of behavioral science

Abstract: The United States intelligence community has been under intense scrutiny from both inside and outside in the aftermath of September 11. Post mortem assessments of intelligence breakdowns may judge the events as more predictable than was in fact the actual reality. In a troubled world, when threats to national security can materialize very quickly, the intelligence community must be able to effectively and swiftly develop and implement plans to prevent further terrorist attacks on the homeland. Numerous scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As members are indoctrinated, the ideology is reinforced by the membership. Busch and Weissman describe the recruitment process: first, groups look for potential believers in the ideology and ensure that the member is completely loyal to the ideology and leaders-completely incorporated as a group member, holding the group's values as his own-before assigning tasks [13]. During this process, the group offers support and belonging to the membership.…”
Section: Applying Left Realism To Terrorismmentioning
confidence: 99%
“…As members are indoctrinated, the ideology is reinforced by the membership. Busch and Weissman describe the recruitment process: first, groups look for potential believers in the ideology and ensure that the member is completely loyal to the ideology and leaders-completely incorporated as a group member, holding the group's values as his own-before assigning tasks [13]. During this process, the group offers support and belonging to the membership.…”
Section: Applying Left Realism To Terrorismmentioning
confidence: 99%
“…Finally, psychologists, with their extensive knowledge of human behavior, can collaborate with criminal justice agencies to develop and test models of criminal behavior, as well as statistically analyze the data collected to determine the accuracy of those models (Stevens, 2005). Similarly, other researchers have suggested that behavioral scientists can and should attempt to better understand terrorist organizations, their leaders, and members in an effort to understand how to dismantle their organizations (Busch & Weissman, 2005). Each of these methods allows for psychologists to be involved with the intelligence-gathering process without compromising their ethical standards.…”
Section: Psychologists As Consultants To Law Enforcement Agenciesmentioning
confidence: 99%
“…and proper employee selection for foreign assignments. Third, by following the recommendations of experts to the intelligence community (Busch and Weissman, 2005), of improving and expanding international management education and training for those assigned to foreign operations.…”
Section: International Terrorismmentioning
confidence: 99%